Homozygous 16p13.11 duplication associated with mild intellectual disability and urinary tract malformations in two siblings born from consanguineous parents. (26th June 2015) - Houcinat, N.; Llanas, B.; Moutton, S.; Toutain, J.; Cailley, D.; Arveiler, B.; Combe, C.; Lacombe, D.; Rooryck, C.
<x xml:space="preserve">Abstract</x> The use of array‐comparative genomic hybridization (array‐CGH) in routine clinical work has allowed the identification of many new copy number variations (CNV). The 16p13.11 duplication has been implicated in various congenital anomalies and neurodevelopmental disorders, but it has also been identified in healthy individuals. We report a clinical observation of two brothers from related parents each carrying a homozygous 16p13.11 duplication. The propositus had mild intellectual disability and posterior urethral valves with chronic renal disease. His brother was considered a healthy child with only learning disabilities and poor academic performances. However, a routine medical examination at 25‐years‐old revealed a mild chronic renal disease and ureteropelvic junction obstruction. Furthermore, the father presented with a unilateral renal agenesis, thus it seemed that a "congenital anomalies of kidney and urinary tract" (CAKUT) phenotype segregated in this family. This may be related to the duplication, but we cannot exclude the involvement of additional genetic or non‐genetic factors in the urological phenotype. Several cohort studies showed association between this chromosomal imbalance and different clinical manifestations, but rarely with CAKUT. The duplication reported here was similar to the larger one of 3.4 Mb previously described versus the more common of 1.6 Mb. It encompassed at least 11 known genes, including the five ohnologs previously identified. Our observation, in addition to expanding the clinical spectrum of the duplication provides further support to understanding the underlying pathogenic mechanism. © 2015 Wiley Periodicals, Inc.